Hodgkin lymphoma: A clinicopathological and immunophenotypic study - Kaumudi Konkay; Tara Roshni Paul; Shantveer G Uppin; Digumarti Raghunadha Rao (Indian Journal of Medical and Paediatric Oncology)
Introduction: The diagnosis of Hodgkin lymphoma (HL) is defined in terms of its microscopic appearance (histology) and the expression of cell surface markers (immunophenotype). Aims and objectives: This study aims to analyze the clinical features, histomorphology, and immunoprofile of over 200 patients of HL diagnosed over a period of 4 years at our institute and to determine relative frequency of various histological subtypes (based on WHO classification) in relation to age and sex distribution in this part of the country. Materials and Methods: All HL cases diagnosed between January 2006 and December 2009 were retrieved from hospital records. The histopathology of both lymph node and bone marrow biopsy (where ever available) along with immunohistochemistry (CD15, CD30, CD20, and ALK) were reviewed. Results: There was a bimodal age distribution. HL affected people a decade earlier than in the western population. The most common presenting complaint was cervical lymphadenopathy. Mixed cellularity was the most frequent subtype (67%), followed by nodular sclerosing subtype (23.5%). Group A (CD15+, CD30+, CD20−), which represents the archetypical immunophenotype of classical HL (CHL) was the most common type (60.6%). The number of CD15 negative CHL was 35.8% and CD20 positive CHL was 17.5%. CD15 negativity with CD20 positivity was seen in 5% CHL. One out of seven CD20 positive CHL patients showed relapse. Conclusion: In this paper, we have discussed in detail about various clinical and histopathological parameters of HL and their relative frequency in various histological subtypes. This paper is being presented as it is a rather large study from India taking into consideration the clinical, pathologic, and immunophenotypic profile of the patients.